THE ROLE OF DIGITAL TECHNOLOGY IN SUPPORTING STUDENTS’ LISTENING SKILLS THROUGH DIGITAL MUSIC PLATFORMS AND PODCASTS: A LITERATURE REVIEW - Salainti, Engelina; Pratiwi, Widya Rizky (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The collaboration of Digital Technology and learning has become one great topic recently. Many people try to search for good ways to support their teaching and learning process through digital technology. Technology has offered many kinds of applications that can help students and teachers. The Music platforms and podcasts consist of many things that can help the students improve their English, especially their English skills. In this literature review, I would like to find and share the role of Digital Technology in supporting students’ Listening through music platforms and podcasts. And the methodology that I would like to use is the qualitative method in which there will be some interviews and videos in collecting the data. And reading through all the results of the interviews and drawing some connections between digital technology and the learning process to analyze the data, the participants are from X Grade students of Makassar Adventists Senior High School. As a result, those students who are active with digital technology, especially the music platforms and podcasts, have better listening skills than those who are not. Here the writer found out that digital music platforms and podcasts can support students’ listening skills.